Variations I: for David Tudor - Cage, John 1912-1992 (Leipzig London New York Peters, 1960)
One score consisting of a title page with performance instructions and 6 transparent sheets containing lines or dots meant to be overlapped to determine composition. Reproduction from a holographic original.
Graphic score
Composed in 1958
Keywords: 20th Century (1901-2000); Aleatory music